Early estimates of SEER cancer incidence, 2014. Issue 13 (14th February 2017) - Lewis, Denise Riedel; Chen, Huann‐Sheng; Cockburn, Myles G.; Wu, Xiao‐Cheng; Stroup, Antoinette M.; Midthune, Douglas N.; Zou, Zhaohui; Krapcho, Martin F.; Miller, Daniel G.; Feuer, Eric J.
Abstract : BACKGROUND: Cancer incidence rates and trends for cases diagnosed through 2014 using data reported to the Surveillance, Epidemiology, and End Results (SEER) program in February 2016 and a validation of rates and trends for cases diagnosed through 2013 and submitted in February 2015 using the November 2015 submission are reported. New cancer sites include the pancreas, kidney and renal pelvis, corpus and uterus, and childhood cancer sites for ages birth to 19 years inclusive. METHODS: A new reporting delay model is presented for these estimates for more consistent results with the model used for the usual November SEER submissions, adjusting for the large case undercount in the February submission. Joinpoint regression methodology was used to assess trends. Delay‐adjusted rates and trends were checked for validity between the February 2016 and November 2016 submissions. RESULTS: Validation revealed that the delay model provides similar estimates of eventual counts using either February or November submission data. Trends declined through 2014 for prostate and colon and rectum cancer for males and females, male and female lung cancer, and cervical cancer. Thyroid cancer and liver and intrahepatic bile duct cancer increased. Pancreas (male and female) and corpus and uterus cancer demonstrated a modest increase. Slight increases occurred for male kidney and renal pelvis, and for all childhood cancer sites for ages birth to 19 years. CONCLUSIONS: Evaluating early cancer data submissions, adjusted for reporting delay, produces timely and valid incidence rates and trends. The results of the current study support using delay‐adjusted February submission data for valid incidence rate and trend estimates over several data cycles. Cancer 2017;123:2524–34. © 2017 American Cancer Society . Abstract : The current study presents a first look at rates and trends for cases in the Surveillance, Epidemiology, and End Results program diagnosed from 2000 through 2014 based on the February 2016 submission. A new variation of the statistical model to correct for incomplete reporting was added this year that demonstrated even better agreement between the prior February and November submissions and that the delay‐adjusted February submission data can be used to produce valid estimates of incidence trends.